Effect of "RIZOKOM-1" and "SERHOSIL" biopreparations on soil moisture in cotton development. - Ismailhodjayev B.Sh; Karamat K.P; Xalmirzayeva B.A; Nasibov B.R; Israilov I.X (Zien Journals, 2023)
This article presents data on the dynamics of changes in soil moisture depending on the season during the cultivation of Namangan-77 cotton variety under the conditions of using the ecologically clean "RIZOKOM-1 and SERHOSIL" biopreparations created on the basis of beneficial bacteria and algae in the conditions of water-saving technologies. The obtained results showed that as a result of the use of biopreparations, it was determined that soil moisture can be preserved more than the control option. Experiments show 15-19% more soil moisture between each watering and 12-15 days longer retention time in satisfactory amounts for the plant
Keywords: Ecological preparations; water-saving technologies; soil; moisture